Evolution and Potential Function in Molluscs of Neuropeptide and Receptor Homologues of the Insect Allatostatins - Li, Zhi; Cardoso, João C. R.; Peng, Maoxiao; Inácio, João P. S.; Power, Deborah M. (Frontiers in Endocrinology, 2021)
The allatostatins (ASTs), AST-A, AST-B and AST-C, have mainly been investigated in insects. They are a large group of small pleotropic alloregulatory neuropeptides that are unrelated in sequence and activate receptors of the rhodopsin G-protein coupled receptor family (GPCRs). The characteristics and functions of the homologue systems in the molluscs (Buccalin, MIP and AST-C-like), the second most diverse group of protostomes after the arthropods, and of high interest for evolutionary studies due to their less rearranged genomes remains to be explored. In the present study their evolution is deciphered in molluscs and putative functions assigned in bivalves through meta-analysis of transcriptomes and experiments. Homologues of the three arthropod AST-type peptide precursors were identified in molluscs and produce a larger number of mature peptides than in insects. The number of putative receptors were also distinct across mollusc species due to lineage and species-specific duplications. Our evolutionary analysis of the receptors identified for the first time in a mollusc, the cephalopod, GALR-like genes, which challenges the accepted paradigm that AST-AR/buccalin-Rs are the orthologues of vertebrate GALRs in protostomes. Tissue transcriptomes revealed the peptides, and their putative receptors have a widespread distribution in bivalves and in the bivalve Mytilus galloprovincialis, elements of the three peptide-receptor systems are highly abundant in the mantle an innate immune barrier tissue. Exposure of M. galloprovincialis to lipopolysaccharide or a marine pathogenic bacterium, Vibrio harveyi, provoked significant modifications in the expression of genes of the peptide precursor and receptors of the AST-C-like system in the mantle suggesting involvement in the immune response. Overall, our study reveals that homologue of the arthropod AST-systems in molluscs are potentially more complex due to the greater number of putative mature peptides and receptor genes. In bivalves they have a broad and varying tissue distribution and abundance, and the elements of the AST-C-like family may have a putative function in the immune response.